The Elusive but Pathogenic Peptidoglycan of Chlamydiae. (January 2013) - Di Pietro, M.; De Santis, F.; De Biase, D.; Sessa, R.
Chlamydia species cause a broad spectrum of diseases in humans including severe chronic sequelae related to persistent forms. Despite the lack of detectable amounts of peptidoglycan, several studies suggest the presence of small quantities of peptidoglycan or its derivative at least in some stages of the growth cycle. Based on recent discovery in Chlamydiae of the aminotransferase pathway for biosynthesis of meso -diaminopimelic acid, we demonstrated the up-regulation of the gene (cp0259) encoding L, L-diaminopimelate aminotransferase in chlamydial persistent forms. This finding may be important in the search for target molecules to diagnose and treat Chlamydia -associated chronic diseases.